"The Elephant, King Of Time" Study Of Linguistic, Semantic Relations, Mythological References and Discourse (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to study the play of " Al –Feel YaMalek Al-Zaman " a symological and lingual study , and to analyze the dramatic speech a symological analysis which clears the signs or the possible images that the dramatic speech may lead to , so that we don't only stop at its lingual limits , but we dive into its semantics to reach that . In an indepth reading of the play of " Al- Feel YaMalek Al- Zaman " we find ourselves  in front of text from the story telling theatre because it gives a story that the audience receive and inter act with it . It is also a text which tries to handle or analyze the relationship of the citizen with authority , and his attitude towards it . The importance of the research is that it studies it studies language as it is the system of communication which includes a great deal of harmony. This system allowed the lingual study to care for the style that Jackson put .( sender – receiver – principles of the theme – its references ) where he enabled the study to go beyond the lingual application which is restricted to a group of characteristics which include the lingual phenomenon to the lingual reading of the texts and other aspects of expression .           يهدف هذا البحث إلى دراسة مسرحية " الفيل يا ملك الزمان " دراسة لغوية سيميائيّة، وتحليل الخطاب المسرحي تحليلاً سيميائيّاً يوضح الدلالات أو التّصورات الممكنة، التي يمكن أن يفضي إليها الخطاب المسرحي، فلا نقف عند حدودها اللسانية اللغوية فحسب، بل نغوص في دلالاتها للوصول إلى ذلك . وفي قراءة متعمّقة لمسرحية " الفيل يا ملك الزمان " نجد أنفسنا أمام نصّ من نوع المسرح الحكواتي؛ لأنه يقدّم حكاية يتلقاها الجمهور، ويتفاعل معها، وهو أيضاً نصّ يحاول أن يعالج أو يحلل (علاقة المواطن بالسلطة، وموقف المواطن السلبي منها) . وتكمن أهمية البحث في كونه يدرس اللغة باعتبارها نظاماً للتواصل يتضمن قدراً كبيراً من الانسجام، سمح للدراسة اللسانية بالاهتمام بالنموذج الذي رسمه جاكبسون ( الباث – المتلقي  - سنن الرسالة – مرجعيتها )؛ ذلك لأنه مكّنها من تجاوز التطبيق اللساني المحصور على جملة محددة من الخصائص التي تشتمل على الظاهرة اللغوية إلى القراءة اللسانية للنصوص ومظاهر التعبير الأخرى . ويعتمد البحث على المنهج البنيوي التكويني في تحليل اللغة، والكلام، والخطاب، تحليلاً ترتيبياً يتناول المستوى الصوتي، الصرفي، النّحوي، والدّلالي، لينتقل إلى ما وراء اللسانيات من بنية سيميائية وتداولية تواصلية ترتبط بالإلقاء في صلته بأهم تقنيات العرض المسرحي لسانيّاً .